Strategi Penguatan Daya Saing Investasi Kota Cilegon melalui Optimalisasi Industri dan Inovasi Pelayanan Publik - Widya Andara (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Cilegon City, located in Banten Province, is recognized as a vital industrial hub contributing to Indonesia's economic growth. However, the city's investment competitiveness still requires substantial enhancement to attract both domestic and foreign investors. This study focuses on developing a strategy to strengthen the investment competitiveness of Cilegon City, primarily through optimizing its industrial sectors and innovating public services. The research adopts a descriptive qualitative approach, using literature reviews, interviews, and observations of local policies and conditions to gather data. The findings suggest that improving investment competitiveness can be achieved through the development of industrial clusters, providing necessary supporting infrastructure, and enhancing public service efficiency, particularly through digitalization and innovations in the licensing process. Additionally, fostering collaboration between local governments, businesses, and the community is essential for creating a competitive and sustainable investment environment. Public service innovation, especially in streamlining the licensing process, increases transparency and builds investor confidence. The study concludes that with an integrated strategy, Cilegon City can transform into a top industrial investment destination with the potential to compete effectively on both national and international levels. This research highlights the importance of strategic planning, innovation, and collaborative efforts in positioning Cilegon as a globally competitive industrial center, enhancing its attractiveness to investors and contributing to economic development.